2012
DOI: 10.1111/rda.12123
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Glycolysis and the Pentose Phosphate Pathway Influences Porcine Oocyte In Vitro Maturation

Abstract: Contents Glycolytic and pentose phosphate pathway (PPP) activities were modulated in porcine cumulus–oocyte complexes (COCs) during in vitro maturation (IVM) by the addition of inhibitors or stimulators of key enzymes of the pathways to elucidate their relative participation in oocyte maturation. The activities of glycolysis and PPP were evaluated by lactate production per COC and by the brilliant cresyl blue test, respectively. Glucose uptake per COC and the oocyte maturation rate were also evaluated. Lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In porcine species, glycolysis appears to be the main fate of glucose during IVM (Krisher et al 2007;Alvarez et al 2012Alvarez et al , 2013. This is consistent with the high activity of PFK detected in porcine COCs remaining to be established the relative participation of this enzyme in oocytes and cumulus cells separately, as mammalian oocytes have low capacity to utilize this substrate (Steeves and Gardner 1999;Purcell and Moley 2009;Sutton-McDowall et al 2010), possibly due to the limited amount of PFK (Cetica et al 2002).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In porcine species, glycolysis appears to be the main fate of glucose during IVM (Krisher et al 2007;Alvarez et al 2012Alvarez et al , 2013. This is consistent with the high activity of PFK detected in porcine COCs remaining to be established the relative participation of this enzyme in oocytes and cumulus cells separately, as mammalian oocytes have low capacity to utilize this substrate (Steeves and Gardner 1999;Purcell and Moley 2009;Sutton-McDowall et al 2010), possibly due to the limited amount of PFK (Cetica et al 2002).…”
Section: Discussionsupporting
confidence: 70%
“…; Alvarez et al. , ). This is consistent with the high activity of PFK detected in porcine COCs remaining to be established the relative participation of this enzyme in oocytes and cumulus cells separately, as mammalian oocytes have low capacity to utilize this substrate (Steeves and Gardner ; Purcell and Moley ; Sutton‐McDowall et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, pharmacological modification of the PPP demonstrated that its activity was associated with meiotic resumption . A prominent role for this pathway in nuclear maturation is supported by additional studies in mice and other species Sakkas 1999, 2005;Herrick at al 2006;Alvarez et al 2013;Gutnisky et al 2014). Kim et al (2012) reported that the PPP is not involved in GVBD in mouse oocytes but, rather, progression beyond MI; however, they tested spontaneous maturation in DOs as opposed to meiotic induction in CEOs, as was the case in our studies.…”
Section: Glucose Metabolism and Meiotic Inductionmentioning
confidence: 88%